Functionalized graphene-based nanomaterials for the removal of lead (II) and bacteria for water and wastewater treatment applications - Musico, Yvonne Ligaya F. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Poly(N-vinylcarbazole) (PVK) was blended with graphene oxide (GO) to form a PVK-GO polymer nanocomposite capable of adsorbing heavy metal from aqueous solutions. The homogenous distribution of GO in the PVK-GO nanocomposite was determined by X-ray photoelectron microscopy (XPS) and attenuated total reflectance-infrared spectroscopy (ATR-IR).The results show that the adsorption capacity of Pb2+ by the nanocomposite increased with increasing amount of GO. This phenomenon was attributed to the increasing concentration of oxygen-containing functional groups available in the nanocomposite. Moreover, the adsorption of Pb2+ onto PVK-GO nanocomposite was influenced by pH changes. Higher pHs had a better adsorption capacity than lower pHs, due to changes in the nanocomposite surface properties. The highest adsorption capacity of the PVK-GO nanocomposite for Pb2+ was 887.98 mg g-1 and fits well the Langmuir model. This adsorption capacity was achieved using a 10: 90 wt% ratio of PVK: GO at pH 7 - 0.5 with a 90 min contact time. The high removal efficiency of this nanocomposite suggests that PVK-GO is effective and can be applied to remove heavy metals from water. Furthermore, surfaces of commercially-available membrane filters were modified by the dispersion of poly(N-vinylcarbazole) (PVK), graphene (G), poly(N_vinylcarbazole)-graphene (PVK-G), graphene oxide (GO), and poly(N-vinylcarbazole)-graphene oxide (PVK-GO) in order to impart the nanomaterials' antibacterial properties and heavy metal removal capacity. Investigations carried out on the surface-modified membrane filters using Escherichia coli and Bacillus subtilis showed that the presence of graphene and graphene oxide-based nanomaterials significantly improved the antibacterial property of the membrane filters. One of the mechanisms for this improved anti-microbial property of the filter was attributed to the production of reactive oxygen species by the nanomaterials. Among the nanomaterials used in this study, the PVK-GO-modified membrane filter exhibited the best removal of B. subtilis and E. coli with 4 and 3 log removals, respectively. The different levels of E. coli and B. subtilis removals were attributed to the differences in their cell structures and composition. In the same way, the presence of graphene and graphene oxide-based nanomaterials on the filter surfaces also significantly improved the heavy metal removal capacity of commercial membrane filters. The regeneration of the modified membrane filters using hydrochloric acid indicates that the filters can be reused for lead removal. The results show that PVK-GO modified membrane filters consistently exhibited superior antimicrobial properties, metal removal capacity, desorption capacity and reusability among all the graphene-based membrane filters investigated. This study demonstrates that PVK-GO modified membrane filters, along with other graphene-based nanocomposite membrane filters, have efficient antibacterial property and high Pb2+ removal capacity that are ideal for water and wastewater treatment applications.
Thesis (Ph.D. in Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Sewage -- Purification -- Heavy metals removal; Graphene oxide